Facile access to chiral ketones through metal-free oxidative C-C bond cleavage of aldehydes by O2 - Tiwari, Bhoopendra (2012)
Giving the metal the boot: The title reaction provides facile access to functionalized chiral ketones from chiral α,α′-disubstituted aldehydes in the presence of molecular oxygen (see scheme). The CC bond-cleavage approach offers an alternative or better method relative to the typical bond-forming strategies used in synthesizing chiral ketones.